Hukum dan Eksistensi Jual Beli Crypto untuk Investasi Dalam Perspektif Ekonomi Islam dan Ekonomi Sosial "Studi Literasi dan Komparasi pada Masyarakat" - Meriyati; Imamul Arifin; Dimas Fahrul Putra Arismanto; Muhammad Rizal; Mustamiruddin (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2023)
In traditional economics, money serves as a universally accepted medium for exchanging goods or services. However, in today's ultramodern economy, cryptocurrencies like Bitcoin have emerged as widely accepted means of payment, wealth accumulation, and value measurement. Despite their potential for simplifying transactions and fostering trade, these digital currencies are viewed cautiously in some contexts. Indonesia, while legalizing Bitcoin and crypto assets, restricts their use as a payment method due to concerns about preserving the value of its national currency and the prevalence of existing e-wallets and mobile banking systems. From an analytical standpoint, investing in cryptocurrencies is recognized as highly volatile, carrying unpredictable risks of value fluctuations. Furthermore, in Islamic Sharia law, such transactions are considered haram lighairihi due to their speculative nature. This research delves into the legal and economic aspects of digital currencies, particularly Bitcoin, highlighting their implications within Indonesia's economic framework while acknowledging their risks and regulatory considerations.Top of Form